2019
DOI: 10.2478/kones-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Strength Analysis of Riveted Joints Using Blind Rivets

Abstract: This article presents results of experimental investigations of the lap blind riveted joint. The main goal of the work is determination of destructive load of the blind riveted joints. The blind rivets were originally used in the aircraft structures where access to both sides of the riveted structure is impossible. Blind rivets are now commonly used in many branches of industry because of their low cost. Moreover, the riveting process is uncomplicated. There are many publications about analysis of strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It was concluded that higher strength of joints was always observed during the shear loading than in the crosstension test. In publication [13] authors examined the strength of riveted joints with a blind rivet for single-row and five-row lap joint, additionally. Moreover for a single-row joint the geometric parameter as size of the hole chamfer was considered.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that higher strength of joints was always observed during the shear loading than in the crosstension test. In publication [13] authors examined the strength of riveted joints with a blind rivet for single-row and five-row lap joint, additionally. Moreover for a single-row joint the geometric parameter as size of the hole chamfer was considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, the influence of the material model on the distribution of stresses and deformations, as well as the influence of other geometric parameters on the load capacity of the riveted joint was not given. From the point of view of this work, the achievements presented in the publication [ 21 ] were very important; the authors analyzed in detail the strength of a single-lap joint with a blind rivet and the influence of the hole chamfer size on the joint load capacity. Shear curves proved that the size of the hole chamfer has a great influence on the strength of the joint and the deformation of the rivet during shear.…”
Section: Introductionmentioning
confidence: 99%